“Epileptic Encephalopathy” of Infancy and Childhood: Electro-Clinical Pictures and Recent Understandings - Parisi, Pasquale (Bentham Science Publishers Ltd, 2010)
There is growing interest in the diagnosis of cognitive impairment among children with epilepsy. It is well known that status of seizures control has to be carefully investigated because it can be sufficient “per se” to cause progressive mental deterioration conditions. Subclinical electroencephalographic discharges may have subtle effects on cognition, learning and sleep patterns, even in the absence of clinical or sub-clinical seizures. In this respect, electroencephalographic monitoring (long-term and nocturnal recording) and in particular an all night video-polysomnography (V-NPSG) record can be crucial to detect the presence of unrecognized seizures and/or an inter-ictal nocturnal EEG discharge increasing. Epileptic encephalopathies (EE) are a group of conditions in which the higher cognitive functions are deteriorate as a consequence of epileptic activity, which, in fact, consists of frequent seizures and/or florid and prolonged interictal paroxysmal discharges, focal or generalized. AEDs represent the first line in opposing the burden of both, the poor seizures control and the poor interictal discharges control, in the cognitive deterioration of EE affected children. Thus, to improve the long-term cognitive/behavioural prognosis in these refractory epileptic children, it should be taken into account both a good seizures control and a strict sleep control, choosing carefully antiepileptic drugs which are able to control not only seizures clinically recognizable but even the EEG discharges onset and its increasing and spreading during sleep. Here, we review the efficacy and safety of the newer AEDs that, to date, are used in the treatment of EE in infancy and childhood.